ANALYSIS OF THE RELATIONSHIP BETWEEN KNOWLEDGE AND HUSBAND SUPPORT WITH THE SELECTION OF LONG-TERM CONTRACEPTIVE METHODS IN WOMEN OF FERTILE AGE AT HELVETIA HEALTH CENTER IN 2024 - Laia, Safitri (TOUR HEALTH JOURNAL, 2024)
Background: Long-term contraceptive methods are family planning programs with the aim of spacing births and regulating the right age to give birth, known to have a high level of effectiveness to delay or regulate pregnancy because it can protect against the risk of pregnancy for a long period of time and has a low failure rate (Marliana, 2022). Long-term contraceptive methods have a higher level of effectiveness than other contraceptive methods, so the Indonesian government in the Population and Family Planning Agency, strives for the participation of more users of long-term contraceptive methods compared to non-long-term contraceptive methods (BKKBN, 2017). Increasing the use of long-term contraceptive methods is an important strategy in efforts to improve reproductive health and reduce the number of unplanned pregnancies. Inaccurate selection of long-acting contraceptive methods by an acceptor can lead to early pregnancy. For example, an acceptor who chooses to use the pill can be at high risk of early pregnancy when compared to the use of other long-term contraceptive methods, because the pill method has a higher chance of early pregnancy if there is negligence of the acceptor in controlling the use of the pill method regularly (Redo, 2021). Purpose: The focus of this study was to determine the relationship between knowledge and husband support with the selection of Long-Term Contraceptive Methods in Women of Fertile Age at the Helvetia Health Center. Methods: In this study, researchers used a descriptive analytic method with a cross sectional design that aims to determine the relationship between knowledge and husband support with the selection of long-term contraceptive methods in women of childbearing age. This research was conducted at the Helvetia Health Center, Medan Helvetia District, Medan City. Informants in this study amounted to 99 women of childbearing age. In this study, researchers used a questionnaire to collect data. Results: Based on the description of the results of research and discussion that has been done, the researcher can draw the following conclusions: There is a significant relationship between knowledge and husband support with the selection of long-term contraceptive methods in women of childbearing age at the Helvetia Health Center. Disscusion and Conclusion: it is recommended for women of childbearing age to actively participate in counseling conducted by the health center and read literature about family planning, especially long-term contraceptive methods to increase their knowledge about long-term contraceptive methods.